β-Cell-Specific Glucocorticoid Reactivation Attenuates Inflammatory β-Cell Destruction - Liu, Xiaoxia; Turban, Sophie; Carter, Roderick N.; Ahmad, Shakil; Ramage, Lynne; Webster, Scott P.; Walker, Brian R.; Seckl, Jonathan R.; Morton, Nicholas M. (Frontiers in Endocrinology, 2014)
Progression and severity of Type 1 diabetes is dependent upon inflammatory induction of nitric oxide production and consequent pancreatic β-cell damage. Glucocorticoids are highly effective anti-inflammatory agents but have been precluded in type 1 diabetes and in islet transplantation protocols because they exacerbated insulin resistance and suppressed β-cell insulin secretion at the high doses employed clinically. In contrast, physiological-range elevation of glucocorticoid action within β-cells ameliorated lipotoxic β-cell failure in transgenic mice overexpressing the intracellular enzyme 11β-hydroxysteroid dehydrogenase type 1 (MIP-HSD1tg/+ mice). Here we tested the hypothesis that elevated β-cell 11beta-HSD1 protects against the β-cell destruction elicited by streptozotocin (STZ), a toxin that dose-dependently mimics aspects of inflammatory and autoimmune destruction. MIP-HSD1tg/+ mice exhibited an episodic protection from the severe hyperglycemia caused by a single high dose of STZ associated with higher and sustained β-cell survival, maintained β-cell replicative potential, higher plasma and islet insulin levels, reduced inflammatory macrophage infiltration and increased anti-inflammatory T regulatory cell content. MIP-HSD1tg/+ mice also completely resisted mild hyperglycemia and insulitis induced by multiple low-dose STZ administration. In vitro, MIP-HSD1tg/+ islets exhibited attenuated STZ-induced nitric oxide production, an effect reversed with a specific 11beta-HSD1 inhibitor. Glucocorticoid regeneration selectively within β-cells protects against inflammatory β-cell destruction, suggesting therapeutic targeting of 11β-HSD1 may ameliorate processes that exacerbate type 1 diabetes and that hinder islet transplantation.